Avaliação da eficiência de remoção de matéria orgânica de um manancial de abastecimento utilizando diferentes tipos de carvão ativado em pó - Souza, Andreney dos Santos de (Universidade Federal do Tocantins, 2024)
Conventional water treatment plants are limited in removing organic compounds. The design of a conventional ETA is the removal of colloidal particles allowing adequate clarification and ensuring microbiological safety. Powdered activated carbon has a very versatile application in water treatment plants and can be used in different concentrations and locations and is directly related to the contaminant to be removed. In this context, this work aimed to evaluate the conditions of use of pulverized activated carbon in terms of the efficiency of removing total organic carbon from raw water from a supply source. The research used the Protimiza software to plan the experiments and adopted the statistical method of delineating centered faces. In total, 11 commercial PAC of vegetable origin were evaluated with an iodine index greater than 600 mgI/g. In the first stage of the tests, all PAC were analyzed. The PAC with the highest efficiency in removing organic matter were selected. The adsorption tests were carried out in the Jar test dosing 20mg/L of a 5% CAP solution and a contact time of 30 minutes. With the selected PAC plus the one used in the ETA, the NPOC (mg/L) and UV-254nm of the tests planned by delineating centered faces were evaluated. In a second stage of the tests, the influence of pre-oxidation with potassium permanganate was evaluated. The treatability tests allowed us to conclude that the powdered activated carbon used in the treatment plant has the lowest organic matter removal efficiency when evaluating the NPOC and UV-254nm parameters and that pre-oxidation with potassium permanganate alters the surface of response of the evaluated PAC.